Tunnel of bones - Schwab, Victoria (Scholastic Inc., 2020)
Now in Paris with her parents who are filming their TV show about the world's haunted cities, Cassidy Blake (who can see ghosts) and her friend Jacob (who is a ghost) are alert for trouble, especially when the filming takes them into the underground Catacombs, the empire of the dead, where Cassidy accidentally awakens a powerful poltergeist spirit--one whose mystery she must solve before his power in unleashed on the whole city.